Selection of computer-integrated manufacturing technologies using a combined analytic hierarchy process and goal programming model - Yurdakul, Mustafa (Robotics and computer-integrated manufacturing, 2004)
Investment in computer-integrated manufacturing (CIM) is a multi-attribute problem, which includes both qualitative and quantitative factors. In order to select the best set of CIM alternatives among the competing ones it is necessary to make a trade off between the quantative and qualitative factors some of which may conflict. Selection of appropriate CIM alternatives is vital in manufacturing companies’ long-term competitiveness, and it requires development of selection models. The selection model must consider various quantative and qualitative objectives and constraints simultaneously. For example, companies have generally limited funds to invest in new advanced technology. The size of the allocated fund limits the types and number of CIM alternatives a company can select in a given time period. In this article, a combined model of the analytical hierarchy process and goal programming is proposed to consider multiple objectives and constraints simultaneously. A real-world example is provided to illustrate the application of the combined approach.